2018
DOI: 10.1177/1461348418765958
|View full text |Cite
|
Sign up to set email alerts
|

Protective earphones and human hearing system response to the received sound frequency signals

Abstract: Sound is one of the most important problems in industrial environments, and it causes hearing loss at different frequencies in the workforce. Incorrect fitting of hearing protector has a negative effect on noise reduction. The present study was conducted with the aim of determination of the effective frequencies on hearing loss and variations of the sound level in different frequencies after placing the earplug. A model of ear canal with different materials was simulated. Sound pressure sensors and earplugs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
3
0
0
Order By: Relevance
“…More in detail, the worsening in the postural performance is particularly evident when subjects are exposed to higher frequencies (1000, 1500, and 2000 Hz) when compared to the quiet condition. These results confirm how, due to the shape of the external auditory canal, the auditory sensitivity of normal hearing humans is greater at frequency signals of 1000-5000 Hz (Ziayi Ghahnavieh et al, 2018) and may suggest that this frequency band would interfere with the vestibular system, reducing its capacity to maintain balance. However, it should be noted that our subjects were not asked to close their eyes during the tests, so they were able to use their visual inputs, other than the other systems, as an alternative source for balance control.…”
Section: Discussionsupporting
confidence: 71%
“…More in detail, the worsening in the postural performance is particularly evident when subjects are exposed to higher frequencies (1000, 1500, and 2000 Hz) when compared to the quiet condition. These results confirm how, due to the shape of the external auditory canal, the auditory sensitivity of normal hearing humans is greater at frequency signals of 1000-5000 Hz (Ziayi Ghahnavieh et al, 2018) and may suggest that this frequency band would interfere with the vestibular system, reducing its capacity to maintain balance. However, it should be noted that our subjects were not asked to close their eyes during the tests, so they were able to use their visual inputs, other than the other systems, as an alternative source for balance control.…”
Section: Discussionsupporting
confidence: 71%
“… 24 It depends on whether or not the respondent loosens the earplugs. 25 Similar study results from Yovi and Suryaningsih 21 showed that the chainsaw operators and harvesting workers have a significantly different perception on the chainsaw sounds in each chainsaw mode (idle, half-gas, racing) and when using or not using ear protectors. This difference might rise because different respondents may react differently to the same stimulus/circumtances.…”
Section: Resultssupporting
confidence: 53%
“…25 It depends on whether or not the respondent loosens the earplugs. 26 Similar study results from Yovi and Suryaningsih 27 showed that the chainsaw operators and non-chainsaw operators have a significantly different perception on the chainsaw sounds in each chainsaw mode (idle, half-gas, racing) and when using or not using ear protectors. This difference might rise because different respondents may react differently to the same stimulus/circumtances.…”
Section: Respondents' Perception Toward Noisesupporting
confidence: 53%